Effect of vitamin K on wound healing: A systematic review and meta-analysis based on preclinical studies - Tang, Saiqing; Ruan, Zhen; Ma, Axue; Wang, Dong; Kou, Jiushe (Frontiers in Pharmacology, 2022)
Background: In recent years, many studies have found that vitamin K is beneficial to wound healing. However, some research results seem to be in conflict. The purpose of this study was to evaluate the effect of vitamin K on wound healing. Methods: We systematically and comprehensively searched the PubMed, Web of Science, Embase, Cochrane library, China National Knowledge Infrastructure (CNKI), VIP and Wanfang eletronic databases. We applied revman5.3 software to calculate the weighted mean difference (WMD) of 95% confidence interval (CI) of animal and cell groups to evaluate the effect of vitamin K on wound healing. Two researchers independently selected studies and used the Cochrane Collaboration tool to assess the risk of bias in the included studies. The overall quality of evidence was assessed using the Recommendation, Assessment, Development and Evaluation (GRADE) working group approach. Results: Among the 1081 articles searched, 6 articles (16 studies in total) met the inclusion criteria. The results of quantitative analysis showed that vitamin K was beneficial to increase the wound healing rate in animal models (rat model: WMD = 27.45 [ 95% CI: 13.46, 41.44]; P = 0.0001), but the opposite result was obtained in cell experiments (WMD =−33.84 [95% CI: −56.90, −10.79]; P = 0.004). Conclusion: This meta-analysis hits that vitamin K could affect the process of wound healing, especially in animal models. While we could not know the clear role at present, which requires larger scale research. In addition, the concentration and safe dose of vitamin K also deserve further study.